Exploring the Challenges Experienced During the Work-integrated Learning of Economic and Management Sciences Student Teachers at a Rural University: A Relational Leadership Approach - Habasisa Vincent Molise; Mapule Yvonne Segooa (Studies in Learning and Teaching, 2024)
Work-integrated learning is the time when student-teachers visit schools to practice their teaching skills. Participation in teaching activities allows student-teachers to apply the theories and principles they learn in lectures. WIL begins at university, when their lecturers supervise student-teachers as they learn about various educational ideas and practices. The study investigates the challenges that economic and management sciences student-teachers face during their WIL, such as a lack of intensive student mentoring, a lack of cordial relationships between student-teachers and mentor-teachers, a lack of clearly defined student expectations, and a lack of commitment from student-teachers and mentor-teachers. A total of five participants were carefully chosen to participate in the study. Semi-structured interviews were used to collect data and gain a thorough understanding. The data was analyzed using thematic analysis. The findings highlighted the necessity of developing partnerships between university and school stakeholders to facilitate the efficient implementation of EMS student-teachers' WILs. University teachers just visit pupils from schools to evaluate them, with little support provided. The mentor instructors also leave student-teachers alone in their classrooms without offering mentorship, viewing the students' presence at school as an opportunity to be free of teaching. The study suggests that the WIL of EMS student-teachers be framed as an archetype within the relational leadership approach to help promote cordial relationships among all involved for it to be successfully implemented and effective.